Cognitive ability in former professional football (soccer) players is associated with estimated heading frequency. Issue 2 (28th October 2021) - Bruno, Davide; Rutherford, Andrew
Abstract : Objectives: The link between football (soccer) headings and dementia risk is a concern given the popularity of this sport worldwide. To assess this link, the cognitive ability of former professional players was tested and self‐reported estimates on heading frequency were collected. Methods: A survey was co‐designed with former players to gather demographics data; information on playing career, including playing position; estimates of total head injuries sustained in training and match play; and estimates of heading frequency during training and match play. Data then were collected by post from 60 males (mean age = 67.5; SD = 9.5), who had played professionally for teams in England. In addition to the survey, each individual also completed the Test Your Memory (TYM) self‐administered cognitive test to evaluate overall ability. Results: Bayesian and traditional linear regression analyses were carried out using the TYM score as outcome. Predictors were estimated career head injuries and estimated career headers, while we controlled for age and reported non‐football head injuries. The results of our analyses showed that estimated career headers, but not estimated career head injuries, predicted TYM scores. Conclusion: To our knowledge, this is the first study to provide direct evidence supporting a link between heading the ball and cognitive impairment in retired professional football players.